Turats fi Tafsir al Qur’an : Makna, Sejarah Perkembangan Dan Manhaj Para Ulama - Pardi, Habib Husnial (STAI Darul Kamal NW Kembang Kerang, 2022)
Various methods and results of interpretation have emerged (according to the times and needs) that can be accessed by the public in understanding the meaning and content of the Qur'an itself. From the aspect of the text, the Qur'an has not changed since it was first revealed until now, but what has changed is the interpretation of the text in accordance with human space and time. Al-Qur'an is always open to analysis, and interpretation with various tools, methods and approaches. Various variants of the Ulama's manhaj regarding interpretation have emerged as a way to explore the meaning of the content contained in the Qur'an itself. on the other hand, the problem of interpretation arises in line with the complexity of human problems. Therefore, this article will focus on the meaning of interpretation, the history of the development of interpretation which is focused on the classical and medieval eras of interpretation and the variants of the manhaj of the scholars. This paper was prepared based on a review of literature or documents using a qualitative approach, type of content analysis method, Klaus Krippendorf (2004). The primary source used is the literature by